MAGNESIUM PREPARATIONS IN PREVENTING ARRHYTHMIAS IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - A. M. Shilov; I. S. Svyatov; V. V. Kravchenko; M. V. Melnik; I. D. Sanodze (Российский кардиологический журнал)
We have investigated the room for magnesium sulfate in preventing arrhythmias in patients with acute myocardial infarction occurring with reperfusion and QT prolongation. We have studied 110 patients in the first 6 hours of AMI, including 50 with QT prolongation and 60 with various regimens of thrombolysis with urokinase. 40 patients received thrombolysis along with magnesium infusion (scheme see infra). Patients with AMI and prolonged QT were infused 20 mL 25% magnesium sulfate in 10 mL 5% glucose for 30 minutes with subsequent intravenous magnesium sulfate 0.5-0.6 g per hour. In all patients plasma and RBC Mg and Ca concentrations were assessed with atomic absorption assay, daily ECG monitoring and 12-lead standard ECG with the analysis of QT duration and dispersion. We have found that patients with AMI in the first 6 hours exhibit a depletion of both serum and intracellular Mg with leads to QT prolongation and dispersion. Magnesium sulfate given intravenously helped reverse QT prolongation by the end of the 2nd day and decrease dispersion significantly. We have also found magnesium sulfate with thrombolysis to decrease the incidence of reperfusion syndrome.